ANALISIS IMPLEMENTASI MODEL PENCITRAAN DAN DAYA SAING INSTITUSIONAL MELALUI MANAJEMEN PENGETAHUAN DAN MODAL SOSIAL - Erna Setijani; Chodidjah Chodidjah (University of Merdeka Malang, 2016)
This study intend to analyse the implementation of institutional image and competitiveness model through knowledge management and social capital. The try out of model supervised periodically for limited small and medium industries in Probolinggo (10 SMEs). Based on the primary data collected during implementation and then analyzed by discriptive and parametrical statistic (compare-means) found that there are significancy differences between before and after model implementation. It means, the created model at this study can be categorized as adaptive model for SMEs in Probolinggo. Therefore, if we want to build corporate image and business competitiveness, this model strongly recommended to be applied. By this way, the small and medium industries will have good image and adequate business competitiveness at the market. Interestingly, the model at this study as standard model and support previous studies that suggest knowledge management and social capital play an important role to build corporate image dan business competitiveness.